Sosialisasi Identifikasi Bahan Tambahan Boraks Pada Kerupuk Di Kabupaten Karimun - Friska Septiani Silitonga; Eka Putra Ramdhani; Okta Alpindo (Universitas Lancang Kuning, 2022)
One of the most produced food products was crackers. Crackers can be made from fish, shrimp, cuttlefish, and others, and cab be sold to improve the community’s economy. For improving the quality and durability of processed seafood products, food additives were added, on of which is preservatives. The problems was occured in the community were: 1) there were still food products that used borax as a preservative, 2) there was no education on how to identify borax in crackers, 3) provide education about the dangers of preservatives to health. The methods used in this activity were: 1) laboratory test for testing with flame test, and 2) the socialization step